Using primary care data for health research in England - an overview - Bradley, Stephen H; Lawrence, Neil R; Carder, Paul (Future healthcare journal, 2018)
In contrast to secondary care, where handwritten records remain widespread, electronic patient records have long been a key feature of UK general practice. By 1996, 96% of general practices were computerised and now almost every primary care consultation in the UK is recorded on a computerised clinical system. Consequently, we now have a vast repository of patient health data that spans decades, which could be used to address a range of important research questions. Unfortunately, accessing primary care data for health researchers can be a burdensome, confusing and time-consuming process. Understanding the way in which primary care data are recorded and 'coded' is not intuitive to those unfamiliar with general practice. The requirements of information governance mean that some data, or data presented in particular ways, are not available at all. This review provides a practical overview of the types of data recorded in primary care, the bodies responsible for them and how they can be accessed.